Int-Soft Filters of BE-Algebras - Sun Shin Ahn; N. O. Alshehri; Young Bae Jun (Discrete Dynamics in Nature and Society)
The notion of int-soft filters of a BE-algebra is introduced, and related properties are investigated. Characterization of an int-soft filter is discussed. The problem of classifying int-soft filters by their γ-inclusive filter is solved.